Genetic improvement of cattle in Colombia, an ideal or a reality? - Amaya, Alejandro; Cotes-Torres, José-Miguel (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Genetic improvement programs in domestic species require a set of steps involving the definition of breeding objectives, information systems, variance component estimation, genetic evaluations, selection indexes, and the estimation of genetic progress and variability. Objective: To identify strengths and weaknesses in the design and implementation of genetic improvement programs in Colombian cattle through scientific and academic contributions derived from research. Conclusion: The greatest challenges in the design and implementation of genetic improvement programs in Colombian cattle are currently related to the absence of consensus breeding objectives among farmers and associations. Additionally, there is a need in the short term to improve both the quality and quantity of information available in databases. Finally, conducting economic analyses that consider genetic parameters is essential for optimizing the response to genetic selection, considering the different productive systems and environmental conditions that Colombia offers.